Implementasi Peran Guru Honorer dalam Meningkatkan Kualitas Pembelajaran di Sekolah Dasar - Gracia Putri Natalia; Mella Tia Tristanti; Maharani Dwi Wahyu Nindiasari; Bayu Purbha Sakti (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
Honorary teachers play an important role in supporting the implementation of education in elementary schools. Their presence helps schools meet the need for teaching staff and ensures that learning activities can be carried out effectively. However, honorary teachers still face various challenges, including limited welfare, uncertain employment status, and restricted opportunities for professional development. These conditions may affect their performance and the quality of learning provided to students. This article aims to describe the implementation of honorary teachers’ roles in improving the quality of learning in elementary schools. The study employed a library research method with a qualitative descriptive approach. Data were obtained from scientific journals, research articles, and other relevant references related to honorary teachers, teacher competencies, and learning quality in elementary schools published between 2020 and 2026. Data collection was conducted through documentation techniques, while data analysis used content analysis involving data collection, reduction, classification, presentation, and interpretation. The findings indicate that honorary teachers perform multiple roles as educators, facilitators, motivators, mentors, and evaluators in the learning process. These roles are implemented through lesson planning, the use of varied teaching methods and learning media, the provision of learning motivation, and continuous learning evaluation. Furthermore, pedagogical, professional, social, and personal competencies contribute significantly to improving learning quality. Despite facing various limitations, honorary teachers make positive contributions to increasing student participation, learning motivation, classroom interaction, and students’ understanding of learning materials in elementary schools.